Student responses to an animated character in information literacy instruction. Issue 1 (19th March 2018) - Poggiali, Jennifer
Abstract : Purpose: This paper reports on a grant-funded project to create a hand-drawn, custom-made animated character named Jasmyn. Drawing on animation theory, the purpose of this paper is to use qualitative research to investigate student responses to the medium of animation, the character's design, and three presentation strategies. Design/methodology/approach: The researchers held three student focus groups to investigate the following research questions: Will students endorse animation as a medium for library instructional videos on the grounds of its entertaining, subversive, or playful qualities? Is Jasmyn designed and written in a way that engages students and compels them to respond to her as a character? How will students respond to three presentation strategies: a lecture-style video, a video with supplemental animations, and a real-time, interactive lesson? Findings: The researchers found that students expressed broad enthusiasm for animation as a medium, though responses to Jasmyn's personality were mixed. The only presentation strategy that prompted unique responses was the interactive session, although all three focus groups provided revealing commentary about online learning. Students also identified aspects of the animation and character that could be improved, and reflected on ways Jasmyn might be integrated into online learning. Research limitations/implications: This study, performed as part of a pilot project, was deliberately small in scale. Clearer implications would emerge from repetition with a larger group of students. Originality/value: Jasmyn may be the only hand-drawn, custom-made animated character created for library instruction. No research studies on the use of animation in libraries have been published to date.